Secja: Fortifikasi kayu secang (Caesalpinia Sappan L) pada minuman instan jahe - Azzahrah, Lulu; Tartar, Sri Udayana; Reta, Reta; Fitri, Muhammad (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Herbal drinks are beverages made by infusing herbs in water, resulting in a drink with dregs. Innovation in food product fortification technology for the processing of ready-to-drink instant herbal beverages can be achieved by converting herbal drinks into instant products. This study aims to analyze the quality of instant herbal drinks, “secja”, enriched with the addition of sappanwood and Emprit Ginger. This study employed a combination of qualitative and quantitative approaches, utilizing a completely randomized factorial design. Data analysis was carried out using the Analysis of Variance (ANOVA) test. The results showed that the quality of instant herbal drinks with the addition of 30 percent sappanwood extract concentration and 10 percent emprit ginger extract obtained a water content of 1.5 percent and a total sugar of 81 OBrix (SNI 011-4320-1996), polyphenols 38.21 mg GAE / 100 g, solubility 25.2 seconds, and hedonic tests of color, aroma, taste got criteria 4 (like).